The relationship between emotional intelligence and leadership in school leaders: a systematic review. - Gómez-Leal, Raquel; Holzar, Allison; Bradley, Christina; Fernández-Berrocal, Pablo; Patti, Janet (Taylor & Francis, 2021)
The purpose of this systematic review is to explore the literature on emotional intelligence related to school leadership using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The authors searched the electronic databases of Eric education, PsycINFO, Scopus and Psychology Database to find relevant articles. They used search criteria to identify a total of 110 references. Using rigorous selection methods, 35 articles were systematically reviewed. The results revealed that emotional intelligence is key for effective leadership and that the most commonly used skills/competences are self-awareness, self-management and empathy. Additionally, the literature makes it clear that the extent to which the leader builds trusting relationships contributes greatly to the development of teacher satisfaction and performance. These findings can help to inform the design of successful pre-service programmes for aspiring leaders and in-service programmes for school principals. Limitations and future lines of research are discussed.
Keywords: Madurez afectiva; Liderazgo en la enseñanza; Emotional intelligence (EI); School leaders; Headteachers; Leadership; School principals